PELATIHAN PEMANFAATAN MEDIA SOSIAL ADSENSE UNTUK MENGOPTIMALKAN IKLAN PRODUK TEPAT SASARAN PADA UMKM KABUPATEN JENEPONTO - Ardimansyah Ardimansyah; Cucut Susanto; Heriadi Heriadi (Yayasan Education and Social Center, 2023)
This Community Service Research, which was funded by the Makassar Dipa University Foundation, is intended as a form of approach offered to overcome the problems that exist in the UMKM assisted group of Vena Energi. The problem that is often faced by MSMEs is in the process of introducing and marketing their products. MSME actors have taken several ways to introduce their products to the public, namely by posting their products to social media such as Facebook, Instagram or via WhatsApp status. However, this did not have an impact on increasing sales of their MSME products, this was because the posts of MSME actors on social media had not yet targeted social media user criteria such as age criteria, location, hobbies, and many other criteria. This can only be done when MSME actors post it in the form of advertisements known as Facebook ads and Instagram ads. For this reason, we, from the team implementing the community service program activities at Dipa Makassar University, have held community service in the form of training for MSME actors in the Vena Energi Jeneponto fostered group, so that they have the skills and ability to advertise and target potential buyers based on criteria that match their MSME products in facebook ads and also Instagram Ads.The result is the creation of MSME actors who are able to utilize Adsense social media to optimize MSME product advertisements so that they are more targeted and able to increase the number of MSME product sales for the Vena Energi Jeneponto fostered group